REGIMES IN THE WINTERTIME CIRCULATION OVER NORTHERN EXTRATROPICS .1. OBSERVATIONAL EVIDENCE - Molteni, F; Tibaldi, S; Palmer, T (1990)
Regimes of the northern extratropical circulation in winter are identified in this paper as clusters of atmospheric states in a low-dimensional phase space generated by the leading EOFs of eddy geopotential fields. Our algorithm seeks points corresponding to local maxima for the density of atmospheric states; subsequently, a cluster is defined around each density maximum as that portion of the phase space in which the observed density can be locally approximated by a unimodal function. Six clusters were found. The largest cluster includes 40% of the field in our sample; but it possesses a positive projection on the Pacific-North American (PNA) pattern. The other five clusters represent anomalous flow regimes and include 52% of the fields. One of them shows a low amplitude of the planetary waves; the remaining four represent states with large wave amplitude but different phases. -from Authors